DNA damage, salivary cortisol levels, and cognitive parameters in a nursing team (2020)
In a cross-sectional study of women in a nursing team at a university hospital in southern Brazil, we studied DNA damage, salivary cortisol levels, and cognition. DNA damage was measured in blood leukocytes with the comet assay and the micronucleus test. Salivary cortisol levels were determined upon waking, 30 min later, and at bedtime. Cognition was evaluated according to the Stroop, Digit span and Word span tests. Cortisol levels on waking up were associated negatively with the number of years the employee worked at the institution and positively with the DNA damage in comet assay. Cognitive scores were lower when the cortisol levels were low at awakening and high at bedtime; and were associated positively with educational level. Cortisol status may influence overall health as well as essential work skills, such as attention.